KORUPSI BANGKRUTKAN NASIONALISME - Santosa, Purbayu Budi (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2011)
Corruption index of Indonesia consistent in high position in the world. Corruption behavior spreadin many aspect and this behaviour had been habit which no wrong. This situation decrease nationalism thatcould be used other part to take benefit from relationship between high corruption and low nationalism. Thissituation is not allow be continued and it must be solved by good leadership and law enforcement.